A novel vibration based breathing crack localization technique using a single sensor measurement. (1st May 2019) - Prawin, J.; Lakshmi, K.; Rama Mohan Rao, A.
Highlights: A breathing crack localisation approach using zero strain energy nodes is proposed. Structure behaviour is concluded using Multi-level singular spectrum analysis. Breathing crack localization is carried out using a single sensor placed anywhere in the structure. The proposed technique is insensitive to the spatial location of load and response. Robustness is demonstrated through numerical and experimental investigations. Abstract: Structural damages such as a fatigue-breathing crack can result in nonlinear dynamical signatures that can significantly enhance their detection. Majority of the existing vibration based breathing crack diagnosis techniques demands rather a dense sensor network in order to detect, precisely locate the spatial location and characterize the breathing crack as the change in the dynamic characteristics of a structure with breathing crack is much smaller when compared to open cracks of the same magnitude. Further, the quality of identification improves with the increase in the number of sensors. In this paper, a novel vibration-based damage detection technique based on the zero strain energy nodes concept is proposed for the first time to identify the exact spatial location of the breathing crack using a single sensor measurement. Two different procedures based on sweep sine and harmonic excitation are outlined for breathing crack localization. Multi-level Singular Spectrum Analysis (M-SSA) is used in the present work to conclude about the presence of nonlinear behaviour of the structure and also for the identification of frequencies at which the cracked structure behaves linearly. Numerical and experimental investigations presented in this paper clearly establish that the proposed approach has the ability to identify single and as well as multiple breathing cracks present anywhere in the structure even with noise contaminated measurements.